Trenton Doyle Hancock - Mind of the mound: critical mass - Markonish, Denise (DelMonico Books, Prestel, 2019)
Trenton Doyle Hancock has transformed his childhood love of comic books, toys, and superhero culture into his own creation myth. That mythology and the fascinating, multimedia iterations that it has sparked are told in this captivating and revealing book. Accompanied by images of his paintings, drawings, and installations alongside pictures of his own vast toy and pop- culture collections as well as pages from his forthcoming graphic novel, the artist traces the birth of the Mounds and Vegans-the plants and mutants that are forever at war-through which he explores good, evil, authority, race, moral relativism, and religion. Hancock takes readers inside his largest exhibition yet at MASS MoCA-a multi-media installation that blends sculpture, painting, and installations to bring the Mounds' world to life. Included in this book are contributions by the exhibition curator Denise Markonish, an art historical essay about Hancock's paintings, and illuminating conversations between Hancock and some of his influences, including Frank Oz. With this book, Hancock merges his personal history with his imagination to create a rich panoply of color, image, and language. Exhibition: MASS MoCA, North Adams, USA (09.03.2019-01.03.2020)
Keywords: Hancock, Trenton Doyle -- 1974-; Bildband; Ausstellungskatalog -- Massachusetts Museum of Contemporary Art -- 09.03.2019-03.11.2019 -- North Adams, Mass.